2020
DOI: 10.3390/jcm9010283
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Malignant Lymphadenopathy Using Flow Cytometry on Fine Needle Aspirate: Report on 269 Cases

Abstract: Introduction: Fine needle aspiration (FNA) is frequently the first noninvasive test used for the diagnostic workup of lymphadenopathy. There have been many studies showing its usefulness, especially in conjunction with other techniques for the diagnosis of lymphoma, but it remains inferior to histological examination. The data regarding this subject have mostly been reported mostly from first-world countries, but are scarce for emerging economies. Thus, the current study assesses the agreement between fine nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…We found that CB acquisition was associated with minimal improvement in diagnostic yield relative to FNA alone, suggesting that addition of CB alone, although helpful, usually does not result in a complete WHO classification of FL at initial diagnosis, and many patients may still require a subsequent, larger biopsy. Flow cytometry has become a standard ancillary diagnostic tool for the identification and subclassification of lymphoma 30,31 . We found a similar rate of repeat biopsies across all three clinical indications evaluated regardless of whether or not flow cytometry was performed, and despite relatively high rates of flow cytometry adequacy across all biopsy types and all clinical indications.…”
Section: Discussionmentioning
confidence: 50%
“…We found that CB acquisition was associated with minimal improvement in diagnostic yield relative to FNA alone, suggesting that addition of CB alone, although helpful, usually does not result in a complete WHO classification of FL at initial diagnosis, and many patients may still require a subsequent, larger biopsy. Flow cytometry has become a standard ancillary diagnostic tool for the identification and subclassification of lymphoma 30,31 . We found a similar rate of repeat biopsies across all three clinical indications evaluated regardless of whether or not flow cytometry was performed, and despite relatively high rates of flow cytometry adequacy across all biopsy types and all clinical indications.…”
Section: Discussionmentioning
confidence: 50%
“…Classic Hodgkin lymphoma (cHL) is an unusual form of lymphoma characterized by a small number of neoplastic Hodgkin and Reed–Sternberg (HRS) cells in an extensive inflammatory background 1,2 . In light of the frequent non‐neoplastic causes of lymphadenopathy and involvement of sensitive locations, lymph node fine‐needle aspiration (FNA) or core needle biopsy (CNB) as minimally invasive procedures are frequently the first alternatives to obtain lymph node tissue to diagnose lymphoproliferative disorders 3,4 . However, insufficient tissue or the relatively sparse distribution of HRS cells decreases the diagnostic accuracy of cHL using conventional histologic evaluation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In light of the frequent non-neoplastic causes of lymphadenopathy and involvement of sensitive locations, lymph node fine-needle aspiration (FNA) or core needle biopsy (CNB) as minimally invasive procedures are frequently the first alternatives to obtain lymph node tissue to diagnose lymphoproliferative disorders. 3,4 However, insufficient tissue or the relatively sparse distribution of HRS cells decreases the diagnostic accuracy of cHL using conventional histologic evaluation. 5 Therefore, more sensitive and efficient ancillary tools such as flow cytometry (FCM) can provide unique diagnostic information when the morphologic analysis is unclear.…”
mentioning
confidence: 99%
“…Cutaneous lymphomas exhibit various clinical, histological, immunophenotypic, and genetic features. Moreover, they differ in prognosis and treatment from systemic lymphomas with similar histological features [ 5 , 6 , 7 , 8 ]. Up to 75–80% of cutaneous lymphomas originate from T-cells, and only 20–25% from B-cells [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%